Workplace Flexibility Practices in SMEs: Relationship with Performance via Redundancies, Absenteeism, and Financial Turnover. (29th December 2013) - Whyman, Philip B.; Petrescu, Alina I.
<x xml:space="preserve">Abstract</x> This workplace flexibility study uses primary data on private sector small and medium‐sized enterprises (SMEs) in Lancashire, United Kingdom, collected in 2009 during the recent "credit crunch" recession. Key features include: (1) objective measures of SME performance; (2) a focus on the previously relatively neglected relationship between workplace flexibility practices (WFPs) and three SME performance indicators, namely, redundancies, absenteeism, and financial turnover; and (3) a timely contribution to research on SMEs. Numerical, functional, and cost WFPs analyses, via zero‐inflated Poisson and linear regressions, control for SME and market characteristics. Despite SMEs having limited resources, the results show a significant section of SMEs to be innovative and entrepreneurial organizations, embracing advancements in employment relations regarding employee discretion, training, participative working arrangements, and/or job security. Moreover, results indicate that WFPs have the potential to assist SMEs in responding to periods of constrained demand. Flexitime and job sharing are associated with low permanent‐employee redundancies. Training, job security, and family‐friendly practices relate to low absenteeism with reductions of up to six annual days per worker. Job security and profit‐related pay are associated with high financial turnover. Staff pay‐freeze links with high financial turnover, but to the detriment of redundancies and absenteeism, whereas management pay‐cuts or management pay‐freeze relate to low financial turnover. On a cautionary note, spending cuts, often enforced by policymakers, may be of limited benefit to SMEs, and thus other approaches would appear more fruitful.